Policy issues in the urban South - Manie Geyer (European Regional Science Association (ERSA), 2003)
This paper will be dealing with elements of global regionalization and how it impacts economically on different groups of developing regions. It will highlight the spatial economic disadvantages Africa is facing in its quest to reconnect to the global economy. Moving its focus to urban South Africa, it will show how different sections of the country's urban population are reacting to local economic conditions vis-à-vis current global economic trends. Based upon the structure of the informal urban economic sector in South Africa and how it has been impacting on the formal urban economic sector in the country over the past fifteen years, the paper will end with an assessment of the possible longer term effects the country's `redesign city'-approach may have on urban economic structural changes in the future.
Keywords: 330